Influencia del uso de las computadoras en la capacidad de logros cognitivos en los alumnos de 11 años de edad con Síndrome de Down del Centro Educativo Especial N° 0001 - TARAPOTO - Paredes Torres, Percy Johan (2013)
The following research was conducted with students from 11 years old of Special Basic Education Center No. 0001, in Tarapoto district, province and department of San Martin. The problem, hypotheses and general objective has been formulated in terms of variables: independent, Computer Use, and dependent measure cognitive ability. The theoretical demonstration by using of Information Technology and Communication to achieve aducational goals and likewise the theoretical support on the Use of Computers for improving the capacity of cognitive achievement in people with Down syndrome, has been applied in matters of Personal Social and Environment Science, Mathematics, Communication and Social Skills curriculum courses that are Special Basic Education Center N°. 0001. Two hypotheses have been made: the alternative hypothesis, which holds that the Computer Use has a significant bearing on the education of people with Down syndrome, while the null hypothesis supports the lak of significant relevance. The study has a quasi-experimental design, we obtained a sample of 12 students, two groups were formed: Experimental and Control, both the first and the second consists of 06 students with Down syndrome, whose variables such as sex, etc. be controlled, the procedure consisted of the implementation of a pre test and post test for both the control group and for the experimental. We performed hypothesis testing results showed significant relevance when doing Computer Use. Consequently the conclusions set its generality, stating that the experimental group significantly improved cognitive achievement capabilities, unlike the control group was significant